Can Work Flexibility and Work Culture Boost Employee Performance? Analysis of the Role of Job Satisfaction - Fatmawati, Fatmawati (International Business Management - Universitas Ciputra, 2024)
This research aims to examine the influence of work flexibility and work culture on employee performance through job satisfaction Jeneponto Regency Population and Civil Registration Service. The sampling technique used a saturated sample of 62 people. The SEM-PLS analysis method was applied using SmartPLS version 3, a software tool commonly used for such analyses. The research results found that work flexibility positively and significantly affects employee performance. Furthermore, work culture has little effect on employee performance. Work flexibility has a positive and significant effect on job satisfaction. Work culture has little effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Work flexibility positively and significantly affects employee performance through job satisfaction. Work culture does not significantly affect employee performance through job satisfaction. This study succeeded in confirming the results of previous research with the aim of extending the applicability of previous research results and having theoretical implications.